RP-HPLC Method for the Estimation of Nebivolol in Tablet Dosage Form - M. K. Sahoo; R. K. Giri; C. S. Barik; S. K. Kanungo; B. V. V. Ravi Kumar (E-Journal of Chemistry)
A reverse phase HPLC method is described for the determination of nebivolol in tablet dosage form. Chromatography was carried on a Hypersil ODS C18 column using a mixture of methanol and water (80:20 v/v) as the mobile phase at a flow rate of 1.0 mL/min with detection at 282 nm. Chlorzoxazone was used as the internal standard. The retention times were 3.175 min and 4.158 min for nebivolol and chlorzoxazone respectively. The detector response was linear in the concentration of 1-400 μg/mL. The limit of detection and limit of quantification was 0.0779 and 0.2361 μg/mL respectively. The percentage assay of nebivolol was 99.974%. The method was validated by determining its sensitivity, accuracy and precision. The proposed method is simple, fast, accurate and precise and hence can be applied for routine quality control of nebivolol in bulk and tablet dosage form.